Air Pollution Exposure and Physical Exhaustion in Relation to GSH:GSSG Ratio of Online-Based Motorcycle Drivers - Nabilla Nurcahya Junior; Dodik Pramono; Fathur Nur Kholis; Lusiana Batubara (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
Background: Online motorcycle drivers work more than 10 hours a day, surpassing the international working hour regulations. Working hours are directly proportional to air pollution exposure generating reactive oxygen species (ROS). On the other hand, physical exercise also contributes to the generation of ROS due to greater oxygen utilization by mitochondria. The ratio of GSH to GSSG represents the oxidative stress level in body tissues.Objective: This study aimed to analyze the relationship between the length of air pollution exposure and the level of physical exhaustion to GSH:GSSG ratio of online motorcycle drivers.Methods: This research was a cross-sectional study of 16 male online motorcycle drivers. The GSH:GSSG ratio was assessed by ELISA with cyclic DTNB reaction principle. Length of air pollution exposure and level of physical exhaustion data were obtained from the interview. Statistical analysis was done to determine the correlation between variables.Results: The mean GSH:GSSG ratio in studied population is 0.69 ± 0.26, lower than 1 value of GSH:GSSG ratio represents high oxidative stress condition. Based on the correlation test, there are no correlation between length of air pollution exposure (r = -0.464, p = 0.070) and level of physical exhaustion (r = -0.439, p = 0.089) to GSH:GSSG ratio in online motorcycle drivers.Conclusion: Our findings suggested that online motorcycle drivers have a high level of oxidative stress, length of air pollution exposure, and status of physical exhaustion, which is not associated with the GSH:GSSG ratio.